1995
DOI: 10.1046/j.1365-2648.1995.21010034.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensing an improvement: an experimental study to evaluate the use of aromatherapy, massage and periods of rest in an intensive care unit

Abstract: There is widespread belief that the use of aromatherapy and massage in an intensive care environment offers a means of increasing the quality of sensory input that patients receive, as well as reducing levels of stress and anxiety. Despite a wealth of anecdotal evidence in support of these claims, there have been few objective studies to evaluate the effects of these therapies. In this experimental study 122 patients admitted to a general intensive care unit were randomly allocated to receive either massage, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
2
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(110 citation statements)
references
References 8 publications
3
99
2
5
Order By: Relevance
“…Diffusers or heat administration of the lavender was not approved by the infectious disease department because of the risk of spreading germs and of heatrelated injuries. Because Dunn et al 6 noted that the effects of lavender were not sustained, placement of the oil of lavender was maintained throughout the night. The oil was premeasured by a study team member before use in the aromatherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusers or heat administration of the lavender was not approved by the infectious disease department because of the risk of spreading germs and of heatrelated injuries. Because Dunn et al 6 noted that the effects of lavender were not sustained, placement of the oil of lavender was maintained throughout the night. The oil was premeasured by a study team member before use in the aromatherapy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Aromatherapy has been used in a variety of settings to assist in relaxation and aid in sleep. In a study of 122 patients in an intensive care unit by Dunn et al, 6 patients exposed to aromatherapy had significantly greater improvements in mood and perceived levels of anxiety than did patients not exposed. In a randomized controlled study 7 in a hospice, the use of lavender and massage resulted in improved sleep scores, but the results were not significant because of the small number of patients in the sample.…”
mentioning
confidence: 96%
“…The purported aroma-therapeutic properties of lavender in healthy individuals have remained as the most controversial application of this essential oil. Proponents of lavender aromatherapy could cite studies like Dunn et al [29] which showed that the use of L. angustifolia essential oil in aroma-therapeutic practices reduced anxiety in intensive care unit patients. Conversely, Howard and Hughes [30] found that expectancy bias limits the objective study of the efficacy of lavender oils in aroma-therapeutic practices.…”
Section: Studies In Human Subjectsmentioning
confidence: 99%
“…To apply juniper essential oil, a diffuser for aromatherapy was used (Aroma breeze NOVA T, ALTA Corporation, Nagoya, Japan). According to previous studies with essential oil, 10 μL of juniper essential oil was pipetted onto a small cotton pad for a diffuse (Dunn et al, 1995). The speed of airflow was 1.2 m/min.…”
mentioning
confidence: 99%